What is the real number of Lyme disease cases in Canada? - N. H. Ogden; C. Bouchard; J. Badcock; M. A. Drebot; S. P. Elias; T. F. Hatchette; J. K. Koffi; P. A. Leighton; L. R. Lindsay; C. B. Lubelczyk; A. S. Peregrine; R. P. Smith; et al. (BMC, 2019)
Abstract Background Lyme disease is emerging in Canada due to expansion of the range of the tick vector Ixodes scapularis from the United States. National surveillance for human Lyme disease cases began in Canada in 2009. Reported numbers of cases increased from 144 cases in 2009 to 2025 in 2017. It has been claimed that few (< 10%) Lyme disease cases are reported associated with i) supposed under-diagnosis resulting from perceived inadequacies of serological testing for Lyme disease, ii) expectation that incidence in Canadian provinces and neighbouring US states should be similar, and iii) analysis of serological responses of dogs to the agent of Lyme disease, Borrelia burgdorferi. We argue that performance of serological testing for Lyme disease is well studied, and variations in test performance at different disease stages are accounted for in clinical diagnosis of Lyme disease, and in surveillance case definitions. Extensive surveillance for tick vectors has taken place in Canada providing a clear picture of the emergence of risk in the Canadian environment. This surveillance shows that the geographic scope of I. scapularis populations and Lyme disease risk is limited but increasing in Canada. The reported incidence of Lyme disease in Canada is consistent with this pattern of environmental risk, and the differences in Lyme disease incidence between US states and neighbouring Canadian provinces are consistent with geographic differences in environmental risk. Data on serological responses in dogs from Canada and the US are consistent with known differences in environmental risk, and in numbers of reported Lyme disease cases, between the US and Canada. Conclusion The high level of consistency in data from human case and tick surveillance, and data on serological responses in dogs, suggests that a high degree of under-reporting in Canada is unlikely. We speculate that approximately one third of cases are reported in regions of emergence of Lyme disease, although prospective studies are needed to fully quantify under-reporting. In the meantime, surveillance continues to identify and track the ongoing emergence of Lyme disease, and the risk to the public, in Canada.